The Role of Parents in Improving Early Childhood Nutritional Status Through Lunch Box Provision - Andini Juniarsih; Fitriana Fitriana; Hesti Putri Setianingsih; Nurhayati Nurhayati (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
Ensuring adequate nutrition for early childhood is a crucial aspect in supporting optimal growth and development. One of the efforts undertaken by parents is providing lunch boxes for children to bring to school. This study aims to analyze the role of parents in improving the nutritional status of early childhood through lunch box provision and to identify the factors influencing menu selection. The research employed a qualitative approach involving 19 children in Group B at Alkhairaat Toboli Kindergarten, along with their parents and classroom teachers. Data were collected through observation, interviews, and documentation, and were analyzed using descriptive qualitative techniques. The findings indicate that most parents have participated in preparing lunch boxes; however, the variety and nutritional content particularly protein sources and vegetables remain limited. Factors influencing lunch box choices include parents’ nutritional knowledge, children’s eating habits, preparation time, and family economic conditions. Teachers also play a role by providing guidance and motivating children to finish their meals. The study concludes that parents play a critical role in ensuring that children’s lunch boxes contain balanced nutrition, including carbohydrates, proteins, fats, vitamins, and minerals. The implications of this research highlight the need for nutrition education for parents, increased menu variation, and strengthened collaboration between schools and families to promote healthy eating habits in young children.